Assessment of vitamin B12 levels among Vitiligo patients - Dayoub, Zeina Adnan; Baddour, Roula Ghazi; Yazji, Haytham Nadra (Journal of medical and pharmaceutical sciences, 2022)
Background: Vitiligo is one of the most common hypopigmented diseases, and is characterized by white patches or hypopigmented macules. The pathogenesis is not completely clear. The pathogenesis hypotheses include the following: autoimmune hypothesis, genetics, oxidative stress, melanocyte depletion, neurological hypothesis, and deficiency of some nutritional factors. Vitamin B12 is one of the most important vitamins of the B group and has many vital roles, the most important roles are in nervous system and blood functions. Vitamin B12 deficiency causes vitiligo by raising the level of homocysteine ​​in the serum, which in turn inhibits the tyrosinase enzyme (responsible for the synthesis of melanin), and stimulates oxidative stress. Objective: To measure the levels of vitamin B12 in patients with vitiligo and compare them with levels in those without it. Research materials and methods: The research sample included 50 patients with vitiligo in all its forms and 50 controls with similar age and gender. The study was conducted in dermatology and venerology clinics at Tishreen University Hospital in Lattakia- Syria. Vitamin B12 (measured by CLIA = chemical luminescence immunoassay) was studied, and its relationship to age, sex, type of vitiligo, disease activity, affected body surface area, and family history of vitiligo were also studied. Laboratory and demographic findings were compared between patients and controls. Results: Vitamin B12 deficiency was found in 31 vitiligo patients versus 13 controls, with a statistically significant difference (P- value=0.0001). There is no relationship between the levels of vitamin B12 in patients with vitiligo and age (P- value=0.8) and sex (P- value=0.7). Vitamin B12 levels are statistically significantly lower in patients with non- segmental vitiligo compared to segmental vitiligo (P- value=0.03). It was statistically significantly lower when more than 20% of the body surface area was affected (P- value=0.8) than when less than 20% was affected, and in patients with stable vitiligo (P- value=0.9). There is no statistically significant relationship between the levels of vitamin B12 and the presence of a family history of vitiligo (P- value = 0.1). Conclusion: The incidence of vitamin B12 deficiency is increased in patients with vitiligo.